(untitled) - H J Sachs (New York, 1978)
This book provodes a complete practical tool for mastering grammatical skills. The explanations of grammatical rules are simple and direct, and prescriptive material is kept to a minimum
Keywords: english language - grammar,english language - problems, exercises, etc